Spectrophotometric Determination of Clonazepam Drug in Pure form and Pharmaceutical Preparation by Diazotization Reaction - S. Alteemi, Hajir; H. Kadim, Kassim (International Journal of Psychosocial Rehabilitation, 2020)
By diazotization coupling reaction as accurate, selective and rapid spectrophotometric method for determination drug of clonazepam by reliant on azo-coupling reaction between CZP and 1,2-phenylenediamine for To achieve the purpose of obtaining the colored product with a maximum absorbance of 480nm. For the conditions, the reaction has been studied and optimized. The linearity range for clonazepam was 0.1–6 µg/ml, while the detections limit 0.04327 quantification limit 0.14425 µg/ml. The molar absorptivity is 8.505×104 L/mol.cm with Sandal's sensitivity of 0.00370 µg/cm². Eventually these methods were successfully completed to determine CZP in pure form and commercial form.